Coevolution of activating and inhibitory receptors within mammalian carcinoembryonic antigen families - Kammerer Robert (BMC Biology, 2010)
Abstract Background Most rapidly evolving gene families are involved in immune responses and reproduction, two biological functions which have been assigned to the carcinoembryonic antigen (CEA) gene family. To gain insights into evolutionary forces shaping the CEA gene family we have analysed this gene family in 27 mammalian species including monotreme and marsupial lineages. Results Phylogenetic analysis provided convincing evidence that the primordial CEA gene family in mammals consisted of five genes, including the immune inhibitory receptor-encoding CEACAM1 (CEA-related cell adhesion molecule) ancestor. Our analysis of the substitution rates within the nucleotide sequence which codes for the ligand binding domain of CEACAM1 indicates that the selection for diversification is, perhaps, a consequence of the exploitation of CEACAM1 by a variety of viral and bacterial pathogens as their cellular receptor. Depending on the extent of the amplification of an ancestral CEACAM1, the number of CEACAM1-related genes varies considerably between mammalian species from less than five in lagomorphs to more than 100 in bats. In most analysed species, ITAM (immunoreceptor tyrosine-based activation motifs) or ITAM-like motif-containing proteins exist which contain Ig-V-like, ligand binding domains closely related to that of CEACAM1. Human CEACAM3 is one such protein which can function as a CEACAM1 decoy receptor in granulocytes by mediating the uptake and destruction of specific bacterial pathogens via its ITAM-like motif. The close relationship between CEACAM1 and its ITAM-encoding relatives appears to be maintained by gene conversion and reciprocal recombination. Surprisingly, secreted CEACAMs resembling immunomodulatory CEACAM1-related trophoblast-specific pregnancy-specific glycoproteins (PSGs) found in humans and rodents evolved only in a limited set of mammals. The appearance of PSG-like genes correlates with invasive trophoblast growth in these species. Conclusions These phylogenetic studies provide evidence that pathogen/host coevolution and a possible participation in fetal-maternal conflict processes led to a highly species-specific diversity of mammalian CEA gene families.